Perspectives of Long Non-Coding RNAs in Cancer Diagnostics - Reis, Eduardo M.; Verjovski-Almeida, Sergio (Frontiers in Genetics, 2012)
Long noncoding RNAs (lncRNAs) transcribed from intergenic and intronic regions of the human genome constitute a broad class of cellular transcripts that are under intensive investigation. While only a handful of lncRNAs have been characterized, their involvement in fundamental cellular processes that control gene expression highlight a central role in cell homeostasis. Not surprisingly, aberrant expression of regulatory lncRNAs has been increasingly documented in different types of cancer, where they can mediate both oncogenic or tumor suppressor effects. Interaction with chromatin remodeling complexes that promote silencing of specific genes seems to be a general mode of lncRNA regulation, but it is conceivable that additional mechanisms of action are yet to be unveiled. LncRNAs show greater tissue specificity compared to protein-coding mRNAs making them attractive in the search of novel diagnostics/prognostics cancer biomarkers in body fluid samples. In fact, lncRNA PCA3 can be detected in urine samples and has been shown to improve diagnosis of prostate cancer. Identification of regulatory regions controlling the expression of lncRNAs highly expressed in tumors (e.g. lncRNA H19) holds potential to the development of targeted cancer therapies based on vectors carrying toxin genes under control of tumor-specific promoters. Annotation and functional characterization of the lncRNA complement of the cancer transcriptome will conceivably provide new venues for early diagnosis and treatment of the disease.